2014
DOI: 10.1016/j.jcrs.2014.01.044
|View full text |Cite
|
Sign up to set email alerts
|

Long-term clinical outcomes of toric intraocular lens implantation in cataract cases with preexisting astigmatism

Abstract: No author has a financial or proprietary interest in any material or method mentioned.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

11
99
2
7

Year Published

2015
2015
2023
2023

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 135 publications
(128 citation statements)
references
References 16 publications
11
99
2
7
Order By: Relevance
“…This might be attributed to the fact that a higher percentage of patients with high myopia (32.35%) have a longer AL. The positive correlation between AL and toric IOL rotation was also observed in our study and in earlier studies [8,[16][17][18]. Although a higher proportion of patients with high myopia were enrolled, the fact that~70% of patients were within 5°of rotation could strongly demonstrate the excellent rotational stability of TECNIS toric IOL.…”
Section: Discussionsupporting
confidence: 88%
See 1 more Smart Citation
“…This might be attributed to the fact that a higher percentage of patients with high myopia (32.35%) have a longer AL. The positive correlation between AL and toric IOL rotation was also observed in our study and in earlier studies [8,[16][17][18]. Although a higher proportion of patients with high myopia were enrolled, the fact that~70% of patients were within 5°of rotation could strongly demonstrate the excellent rotational stability of TECNIS toric IOL.…”
Section: Discussionsupporting
confidence: 88%
“…Moreover, several studies have mentioned the correlation between AL and rotational stability. Most studies have indicated that AL is positively related with axis misalignment [8,[16][17][18], while Klamann et al [21] have reported that no significant correlation exists between AL and total absolute rotation. We, for the first time, measured LT using A-scan ultrasound that could directly represent the diameter of capsular bag compared with AL.…”
Section: Discussionmentioning
confidence: 99%
“…27 Chang et al 5 performed surgical repositioning in 3 eyes at 5 to 14 days after cataract surgery and obtained good results. Miyake et al 10 reported favorable results of repositioning surgery performed at an average of 8.6 days (range, 2e19 days) after cataract surgery. They also showed that toric IOLs had the greatest rotation in the early postoperative period with little rotation after 1 week.…”
Section: Discussionmentioning
confidence: 99%
“…6 Other studies reported that the incidence of repositioning surgery after AcrySof toric IOL implantation was 2 of 111 eyes, 7 4 of 122 eyes, 8 1 of 82 eyes, 9 and 7 of 378 eyes. 10 Of 172 eyes implanted with TECNIS toric IOLs (Abbott Medical Optics, Inc., Santa Ana, CA), realignment surgery was performed in 4 eyes (2.3%) during a 6-month clinical trial. 11 TECNIS toric IOLs have been repositioned in 4 of 174 eyes 12 and 2 of 27 eyes.…”
mentioning
confidence: 99%
“…It was suggested that larger capsular bags might reduce the equatorial friction for a given IOL, and therefore, decrease IOL stability 19. In addition, patients with a longer AXL might be implanted with an IOL with a lower spherical power, which is thinner, and could decrease IOL stability 11. Besides, though not identified in the current study, high myopia with a longer AXL is known to be related to zonular weakness, which can also affect the rotational stability 20 21.…”
Section: Discussionmentioning
confidence: 99%